Redox reactions control Cu and Fe isotope fractionation in a magmatic Ni–Cu mineralization system. (15th March 2019) - Zhao, Yun; Xue, Chunji; Liu, Sheng-Ao; Mathur, Ryan; Zhao, Xiaobo; Yang, Yongqiang; Dai, Junfeng; Man, Ronghao; Liu, Ximeng
Abstract: Copper and Fe are redox-sensitive metals, and their isotopic compositions may potentially record changes of oxidation conditions in high-temperature magmatic Ni–Cu mineralization systems. High-precision Cu and Fe isotope data for sulfides (chalcopyrite) and whole-rock samples of the Tulaergen magmatic Ni–Cu system (NW China) were analyzed to evaluate redox-induced fractionation during segregation of sulfide melt from silicate melt and internal fractionation within segregated sulfide melt. Sulfide mineralization includes disseminated and massive types, with massive sulfides being further divided into Cu- and Fe-rich ores. Numerical modeling using mass-balance and Rayleigh equations indicate that disseminated sulfide mineralization was generated from a common parental magma, and massive sulfides were formed by monosulfide solid-solution (MSS)–residual sulfide liquid fractionation. During segregation of sulfide melt from silicate melt, crystallization of olivine and pyroxenes with sulfide segregation, in an Fe 2+ -dominated phase, led to the incorporation of lighter Fe isotopes in these minerals. The residual silicate melt became progressively more oxidized, with δ 56 Fewhole-rock values increasing as melts evolved. The disseminated chalcopyrite formed in early stages has lighter Cu and heavier Fe isotopic compositions than the disseminated sulfides formed in later stages due to charge-balance effects. Minor accumulated Ni–Cu sulfide melt was fractionated into an Fe-rich MSS cumulate and a Cu-rich sulfide liquid. MSS crystallization caused the oxygen fugacity of the evolved sulfide liquid to increase, which was accompanied by increasing δ 65 Cu and decreasing δ 56 Fe values in chalcopyrite. Iron isotopic compositions of the whole system were shifted towards heavier values from MSS cumulate to the evolved sulfide melt. Numerical modeling using the Rayleigh equation indicates that the fractionation factors α 65 Curesidual sulfide melt–MSS and α 56 Feresidual sulfide melt–MSS are ∼1.0011 and ∼1.0005, respectively, during internal fractionation within segregated sulfide melt. This study demonstrates that redox reactions play a key role in Cu and Fe isotope fractionation in high-temperature magmatic Ni–Cu mineralization systems. Furthermore, Cu and Fe isotopes can be used to trace concealed orebodies. Elevated δ 65 Cu and δ 56 Fewhole-rock values may indicate Cu-rich mineralization potential, while light Cu and Fe isotopic compositions imply favorable hosts for disseminated and Fe-rich orebodies in mafic–ultramafic intrusions.